The Role Of CEO Altruism in Moderating The Relationship of Workload and Work-Related Fatigue with Employee Retention in Furniture Manufacturing Small and Medium Enterprises - Wahyuni, Dwi Puji; Pratami, Andita Fitri; Permanik, Edis Dian; Siddiq, Dedi Muhammad; Syahroni, Bachrudin; Setapa, Mariam (International Journal of Business, Economics, and Social Development, 2024)
Chief Executive Officer (CEO) altruism as the behavior of small and medium enterprises’ (SMEs) CEOs to improve employee welfare that it is not stated in employment agreement is believed to play a role in increasing retention in employees. This study aims to examine the extent to which the role of CEO altruism in moderating the relationship of workload and work-related fatigue with employee retention of rattan industry companies. Respondents in this study were 250 employees of rattan SMEs in Indonesia. Data were collected through surveys by distributing paper-based questionnaires to employees spread across several rattan SMEs. Using moderated regression analysis techniques by SPSS, this study found that workload and work-related fatigue have a negative impact on employee retention. Furthermore, this research also found that CEO Altruism successfully moderated the relationship of workload and employee fatigue with employee retention.